Overview on natural dyes and their IR-spectra - Part IV: Dyes originated from insects - Boris Mahltig (Communications in Development and Assembling of Textile Products)
Natural dyes were important in the past of textile industry. Due to actual trends towards bio-based and sustainable materials, also natural dyes might face a revival as part of a new sustainable clothing industry. According to this statement, the current paper gives an overview on selected natural dyes which are originated from insects. Altogether three different types of dyes are discussed gained from three different types of lice – cochineal, lac and kermes lice. Additional to an overview on dye properties and applications, a special view is done on the infrared spectra recorded from those dye materials. The IR-spectra are discussed in relation to chemical composition and structure of dye materials. They are a helpful tool for people working in the field of dye identification and quality control. The intension of this review series is to support an overview on natural dyes and their IR-spectra.